A Digest of the Laws and Ordinances of the City of Philadelphia, at 462, Bureau of Corrections, pt. 3, § 80 (1887) - (:unkn) unknown (My University, 1879)
Any tramp who shall enter any dwelling-house, against the will or*§without the permission of the owner or occupant thereof, or shall kindle any fire in the highway, or on the land of another, without the owner's consent, or shall be found carrying any fire-arms or other dangerous weapon, with intent unlawfully to do injury or intimidate any other person, which intent may be inferred by the jury trying the case, from the facts that the defendant is a tramp, and so armed, or shall do, or threaten to do, any injury, not amounting to a felony, to any person, or to the real or personal estate of another, shall, upon conviction, be deemed guilty of a misdemeanor, and shall be sentenced to undergo an imprisonment by separate or solitary confinement at labor for a period not exceeding three years."
Keywords: CARRY - INTENT TO COMMIT CRIME